Penerapan Keamanan Siber pada Sistem Transportasi Laut - Sahrudin Sahrudin; Muhamad Bahrul Ulum (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Marine transportation systems are increasingly dependent on computing and communication technologies, Information technology (IT) and operational technology (OT) must work together to protect information and design security against criminal activity from cyberattacks. A system of process stages and cybersecurity assessments for ships is necessary so that the vulnerability of marine transport systems to cyberattacks can be measured accurately and effectively. Using the framework NIST, The CIA model and Risk Assessment Matrix (RAM) for identification and measurement is the most important key in the cybersecurity assessment process of marine transport systems. With the scope of analysis on vessel infrastructure including network systems, computers, ship communication devices, testing, and assessment.